Aggressive central giant cell granuloma of the mandible, a diagnostic dilemma - Pavitra Baskaran; Margathavalli Gopal; Varun Rastogi; Satya Ranjan Misra (Wolters Kluwer Medknow Publications, 2015)
Central giant cell granuloma (CGCG) of the jaw bones is a rare benign intraosseous lesions that is commonly seen as indolent lesions in the mandible anterior to the first molar. It is a localized osteolytic lesion with the varied biologic behavior of aggression which affects the jaw bones. There is much controversy regarding it arising as a result of trauma and its connection with the giant cell lesion seen in the long bones. Since the lesion is uncommon, does not possess any characteristic clinical or radiologic features, and resembles neoplasms, the diagnosis is initially some odontogenic or non-odontogenic neoplasm till a definitive histologic diagnosis of CGCG is made. CGCG is divided into a rare aggressive variant and a common nonaggressive variant based on the clinical and radiographic features. The present case is a rare aggressive CGCG seen in the posterior mandible associated with mandibular swelling, rapid growth, pain, paraesthesia, and cortical bone perforation.